PetGrab- linker services – a conceptual business model - Ahmad Dahlan, Abdul Rahman; Abd Rahman, Muhammad Taufiq Syahmi; Mohd Fadil, Muhammad Alif (IEEE, 2018)
the objective of this paper is to propose and introduce to people an apps that will help to link between clinic and pet owners. petGrab aims is to help user which are the pet owners to get their pets treatments in order to make sure their pets healthy. In this paper also, we propose the Business Model Canvas (BMC), strategy canvas, environmental map and value proposition design (VPD). This is a conceptual solution that been proposed. Other than that, this paper also has proposed enhanced BM.